Lyman Judy Carlock papers - Carlock, Lyman Judy, 1867-1903.
Correspondence, diary (190l), legal papers, scrapbook, clippings, printed material, and memorabilia, largely relating to Carlock's service as judge in the Philippines (l90l-1903). Later papers concern his death and estate. Correspondents include Joseph V. Graff and William Howard Taft.
Lawyer and judge.
Collection material in English, with Spanish.
Keywords: Graff, Joseph Verdi, -- 1854-1921 -- Correspondence; Taft, William H. -- 1857-1930 -- Correspondence; Judges -- Philippines; Jurists; Lawyers